Why equity in health and in access to health care are elusive: Insights from Canada and South Africa. Issue 11 (2nd November 2018) - Benatar, Solomon; Sullivan, Terrence; Brown, Adalsteinn
ABSTRACT: Health and access to health care vary strikingly across the globe, and debates about this have been pervasive and controversial. Some comparative data in Canada and South Africa illustrate the complexity of achieving greater equity anywhere, even in a wealthy country like Canada. Potential bi-directional lessons relevant both to local and global public health are identified. Both countries should consider the implications of lost opportunity costs associated with lack of explicit resource allocation policies. While National Health Insurance is attractive politically, Canada's example cannot be fully emulated in South Africa. Short- and medium-term attempts to improve equity in middle-income countries should focus on equitable access to insurance to cover primary health care and on making more use of nurse practitioners and community health workers. In the longer-term, attention is needed to the economic and political power structures that influence health and health care and that ignore the social and societal determinants of sustainable good health locally and globally. This long-term vision of health is needed globally to achieve improvements in individual and population health in a century characterised by limits to economic growth, widening disparities, continuing conflict and migration on a large scale and multiple adverse impacts of climate change.